STRATEGY OF ASSET MANAGEMENT FOR HEAVY EQUIPMENT AT PUBLIC WORK SERVICE OF NORTH BARITO REGENCY - Feri Edi Purwanto (Jurnal Teknologi Berkelanjutan, 2014)
The Public Work Service of North Barito Regency manages 46 units of heavy equipment comprising of 10 types, of which 9 are in good condition, 6 in fair condition and 31 are severely damaged. The lack of funding is often pointed out as the cause of minimum optimization of the heavy equipment management. To make matters worse, all the units are old and obsolete. This issue will burden the operation as well as the maintenance. Therefore, methods to optimize the heavy equipment asset are in demand, one of which is by looking for better management alternatives. This research aims to find alternative strategies in managing the heavy equipment assets of the Public Work Department of North Barito Regency, by analyzing their condition based on the technical aspects, funding, legality and management. This research uses descriptive analyses to portrait the existing condition of the heavy equipment management by the Public Work Service of Barito Utara Regency, the analyses of interest (expectation) and perception (reality) level, and SWOT analyses to formulate the strategy to optimize the management of the heavy equipment. Data collection was carried out in two phases, which is by direct observation, interview and questionnaire with respondents which include users/plant hire companies, and some public officials related the equipment management. Based on this research, the analysis of the interest level (expectation) and perception (reality) shows that the average level of perception is 2.52, and the average level of expectation is 3.44. This result indicates that the managers are still unable to provide a good service, and the users of heavy equipment have not received a satisfying service. Furthermore, the SWOT analysis generates S-O strategy (Aggressive) with 7 alternative strategies that attempt to use force to take advantage of existing opportunities. The alternative strategies are to utilize the functionality of workshops with various equipment activities recommended to support infrastructure, to improve service quality of heavy equipment with excellent service orientation, to utilize all available facilities, to empower human resources for the common good, and to develop an adjustment plan with potential targets revenue from the heavy equipment rental.